Are There Long-Term Effects on Wages When Graduating in A Bad Economy in Taiwan? - Liu, Hsiang-Yin; Chen, Jennjou (Asian Economic and Financial Review, 2014)
Entering labor market during a bad economy can be intuitively connected to worse working experience at the beginning of one’s career, and moreover, the effect would persist for many years to come. We empirically estimate the long-term effect of graduating in a bad economy on wages in Taiwan. The estimation results do show significant evidences of negative long-term effect on wages. Besides, the long-term effects vary across genders and education groups.